Traumatic brain injury induced temperature dysregulation: What is the role of β blockers?. Issue 1 (January 2021) - Asmar, Samer; Bible, Letitia; Chehab, Mohamad; Tang, Andrew; Khurrum, Muhammad; Castanon, Lourdes; Ditillo, Michael; Douglas, Molly; Joseph, Bellal
Abstract : BACKGROUND: Traumatic brain injury (TBI) is associated with sympathetic discharge that leads to posttraumatic hyperthermia (PTH). Beta blockers (ββ) are known to counteract overactive sympathetic discharge. The aim of our study was to evaluate the effect of ββ on PTH in critically-ill TBI patients. METHODS: We performed retrospective cohort analysis of the Medical Information Mart for Intensive Care database. We included all critically ill TBI patients with head Abbreviated Injury Scale (AIS) score of 3 or greater and other body region AIS score less than 2 who developed PTH (at least one febrile episode [T > 38.3°C] with negative microbiological cultures (blood, urine, and bronchoalveolar lavage). Patients on preinjury ββ were excluded. Patients were stratified into (ββ+) and (ββ−) groups. Propensity score matching was performed (1:1 ratio) controlling for patient demographics, injury parameters and other medications that influence temperature. Outcomes were the number of febrile episodes, maximum temperature, and the time interval between febrile episodes. Multivariate linear regression was performed. RESULTS: We analyzed 4, 286 critically ill TBI patients. A matched cohort of 1, 544 patients was obtained: 772 ββ + (metoprolol, 60%; propranolol, 25%; and atenolol, 15%) and 772 ββ−. Mean age was 63.4 ± 15.4 years, median head AIS score of 3 (3–4), and median Injury Severity Score of 10 (9–16). Patients in the ββ+ group had a lower number of febrile episodes (8 episodes vs. 12 episodes; p = 0.003), lower median maximum temperature (38.0°C vs. 38.5°C; p = 0.025), and a longer median time between febrile episodes (3 hours vs. 1 hour; p = 0.013). On linear regression, propranolol was found to be superior in terms of reducing the number of febrile episodes and the maximum temperature. However, there was no significant difference between the three ββ in terms of reducing the time interval between febrile episodes ( p = 0.582). CONCLUSION: Beta blockers attenuate PTH by decreasing the frequency of febrile episodes, increasing the time interval between febrile episodes, and reducing the maximum rise in temperature. ββ may be a potential therapeutic modality in PTH. LEVEL OF EVIDENCE: Therapeutic, level IV.